College Library Management in the Digitalization Era - Baihaqi, Moh. Hamdan; Susetiyo, Ari (Program Pascasarjana Institut Agama Islam Darullughah Wadda'wah Bangil Pasuruan, 2024)
The library is the door to knowledge, among students the word library is a way for students to gain broader insights. The purpose of this study is to discuss library management in the digital era. This study uses a descriptive qualitative method. Data collection is carried out by field observation methods, interviews and documentation on each relevant object according to what is needed in the study. In using this qualitative method, many things may change and have profound possibilities. The results of this study include: digital technology has helped facilitate library management in planning the use of recording administration at Tribakti Islamic University of Lirboyo Kediri. In addition, observations related to the influence of the digital era on school libraries have influenced the technical services of school libraries at Tribakti Islamic University of Lirboyo Kediri, which is part of the implementation of planning for college libraries.